The influence of entrepreneur characteristics for fashion business success - Khansa, Fairaniah; Bekti, Rudy (Journal of Innovation, Business and Entrepreneurship, 2019)
Fashion is the second largest contributor to the GDP of the creative industry with a figure of 18.1%. During the period of 2015-2018, in Indonesia, many fashion brands have sprung up with a total growth of 7.05%. And now fashion brands can be said to be 5 points 1, which means that one small scope has at least 5 fashion brands, which results in increasingly tight competition. This research aims to explore the characteristics of fashion entrepreneur. Based on the results, the researcher found there are 6 characteristics that influence the business success. This research used qualitative approach which is in-depth interview method. It conducted to 10 business owners in the fashion industry in Bandung and Jakarta. In exploring the influence between entrepreneur characteristics and business success, there are 4 main dimensions related to business success.. According to the results of the in-depth interview, it was found that all fashion entrepreneurs who become informants have all the good entrepreneur characteristics and also their characteristics turned out to really affect the success of their business where all four dimensions of business success can be achieved by all informants. According to the research results, there are several recommendations that can be applied at SADE in terms of improving the quality of the characteristics of entrepreneurs and recommendations for achieving business success. SADE must implement the six characteristics of entrepreneurs related to business success in each member, and SADE has to create improvements to the four dimensions of business success in their businesses.Keywords: Business Success, Entrepreneur, Entrepreneurship, Entrepreneur Characteristics, Fashion Industry , SMEs